P–115 Supplementation of healthy Sertoli cells into culture media containing follicle stimulating hormone (FSH)/testosterone (T) has no advantage in germ cell maturation. (6th August 2021) - Aydos, S; Yukselten, Y; Ozkan, T; Ozkavukcu, S; Erdogan, M; Sunguroglu, A; Aydos, K
Abstract: Study question: In nonobstructive azoospermia (NOA) cases, whether supplementation of healthy Sertoli cells (SCs) has an effect on spermatogenic differentiation in culture medium containing FSH/T. Summary answer: Expression of Crem and Acrosin increased significantly in both medium with FSH/T and medium with additional healthy SCs but there was no difference between them What is known already: In NOA the induction of spermatogonial stem cells (SSCs) proliferation and differentiation has been demonstrated using different culture systems. SCs have vital roles in the regulation of spermatogenesis. Hormonal control of spermatogenesis is through FSH and T activity on SCs. Growth factors secreted by SCs via FSH, stimulate proliferation and colonization of SSCs. Although germ cells do not express androgen receptors, FSH receptors are localized on spermatogonia. It is not clear whether native SCs are sufficient for FSH/T added to the culture medium to be effective in induction of spermatogenesis, and whether supplementation of healthy SCs will increase this activity. Study design, size, duration: 34 NOA and 12 obstructive azoospermia (OA) cases were included. Testicular tissue samples were taken with testicular sperm extraction (TESE) in the study and control groups. In a group of fertile cases, healthy Sertoli cells were identified and purified and then cryopreserved. Tissue samples of each case prepared in standard DMEM/F12 medium were processed in 2 separate environments containing FSH/T and FSH/T plus thawed healthy SCs for 7 days. Participants/materials, setting, methods: The characterization of healthy SCs isolated from fertile cases was done by flow cytometry (FC) and immunohistochemistry using antibodies specific for GATA4 and vimentin. FITC-conjugated annexin V/PI staining and MTT assay were performed to compare the viability and proliferation of SCs before and after freezing. FC was used to measure the 7th day levels of specific markers expressed in spermatogonia (Vasa), meiotic cells (Crem) and post-meiotic cells (Protamine–2 and Acrosin). Main results and the role of chance: In Annexin V staining, no difference was found in percentages of live and apoptotic SCs, and MTT exhibited that cryopreservation didn't inhibite the SCs proliferation compared to the pre-freezing state. Vasa and Acrosin basal levels were found to be lower in infertile patients compared to the control group (8.2% vs. 30.6% and 12.8% vs. 30.5%, p < 0.05). Compared to day 0 measurements, on the 7th day in FSH/T environment, Crem level increased by 58.8% and Acrosin level increased by 195.5% (p < 0.05). Similarly, in medium supplemented with healthy SCs, by day 7, the Crem and Acrosin levels were increased to 92.2% and 204.8%, respectively (p < 0.05). Although Vasa and Protamine levels increased in both groups, they did not reach a significant level. No significant difference was found between the 7th day increase rates of Crem, Vasa, Acrosin and Protamine–2 in either FSH/T-containing medium or in medium additionally supplemented with healthy SCs (58.8% vs. 92.2%, 120.6% vs. 79.4%, 195.5% vs. 204.8% and 232.3% vs. 198.4%, respectively, p > 0.05). Our results suggest that freezing-thawing process would not impair the viability and proliferation of SCs, and adding healthy SCs to the culture medium to correct impaired gene expression does not have an advantage over FSH/T. Limitations, reasons for caution: The 7-day culture period we determined might be not sufficient for spermatogenic differentiation completion. This period could be extended in order to see further morphological differentiation may need. Wider implications of the findings: The failure of the culture media containing FSH/T to show the expected effectiveness could be thought to be due to the SCs' inadequate response to these hormones. Therefore, healthy SCs supplementation would be needed, but this could pose ethical issues. Our findings show that it is not necessary. Trial registration number: 214S532